(untitled) (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
N.O. Ashukina made a significant contribution to the bot of the trade union of the Sytenko Institute of Spine and Joint Pathology National Academy of Medical Sciences of Ukraine, Kharkiv, The functioning of the internal audit system organization and information support branches of the institution in international scientometric bases.